Identifikasi Organisme Pengganggu (OPT) pada Tanaman Jeruk (Citrus reticulata) - Nurmasari, Fitri; Syaifudin Aswan, Mohamad (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2026)
Plant-disrupting organisms (OPT) are the main factors that influence the productivity and quality of citrus plants (Citrus reticulata). This study is conducted to identify the types of pests and diseases that inhibit citrus plants in the Banyuwangi Regency area as a first step in developing a more effective pest management strategy. The method used in this study is a survey method with data collection in the form of direct observations in the field of citrus plants, including morphology identification, attack symptoms and intensity of pest presence. Furthermore, the data were tabulated and analyzed, then described descriptively. The results of the study obtained seven species of insect pests found on citrus plants, they were Toxoptera citricida, Aphis spiraecola, Planococcus citri, Diaphorina citri, Panonychus citri, Scirtothrips citri, and Bactrocera dorsalis. Six main types of disease were also found through the study, including Citrus Vein Phloem Degeneration (CVPD), Root & Base Rot Disease (Phytophthora Root Rot/Gummosis), Diplodia Dieback Disease, Fruit Rot Disease (Anthracnose/Diplodia Fruit Rot), Citrus Scab Disease (Citrus Cancer), and Tristeza Disease (Citrus Tristeza Virus–CTV). These results confirm the complexity of pest attacks on orange plantations in Banyuwangi is quite high so that sustainable implementation of integrated pest management (IPM) is needed to reduce damage and maintain local orange productivity